Family business branding : communicating a family-based brand identity - Elbanna, Karim; Hakala, Henna-Leena (2017)
Scholars suggest that family-owned businesses can capitalize on their family ties by promoting the fact that they are family-owned in their marketing communications. Existing research suggests that promoting the familial component of a family-owned business can evoke positive associations with the business' stakeholders, increase employee loyalty and motivation, and be a source of competitive advantage against non-family businesses. Although there is an increasing awareness that family-owned businesses can benefit from promoting the fact that they are family-owned in their marketing and branding efforts, very little literature exists on how such a strategy is effectively implemented. By applying qualitative research methods, this study aims to determine how small to medium-sized Finnish family-owned businesses promote the familial component of their business in their branding strategies, why they do so, and how communicating a family-based brand is seen by the company communicating it and its stakeholders. In this study, the data was collected by conducting eight in-depth interviews, seven of which were conducted with informants from small to medium-sized Finnish family-owned businesses, and one with a marketing specialist from a branding agency. The findings of this study suggest that a family-based brand identity can be effectively communicated through oral discussion, and by creating a family-like atmosphere at the workplace. The findings reveal that a family-based brand identity promotes trust and creates close and loyal relations with stakeholders of the company projecting it, and that it can positively affect employee motivation and loyalty, especially when companies promote a family-like atmosphere at the workplace. This study provides managerial implications regarding strategies family-owned businesses can utilize to communicate a family-based brand identity and enhance the benefits it creates for the business and its employees. In addition, future research opportunities are discussed and presented.